PO-15 - Antiangiogenic small molecule ligands of FGF2 derived from the endogenous inhibitor thrombospondin-1. Issue 140 (April 2016) - Pinessi, D.; Foglieni, C.; Bugatti, A.; Moroni, E.; Resovi, A.; Ribatti, D.; Rusnati, M.; Giavazzi, R.; Colombo, G.; Taraboletti, G.
Abstract : Introduction: Platelet thrombospondin-1 (TSP-1) is a major endogenous regulator of growth factor activity in physiological and pathological processes, including tumor onset, progression and angiogenesis. We previously demonstrated that TSP-1 binds to FGF-2, sequestering the growth factor and inhibiting its angiogenic activity. We also identified a non-peptidic antiangiogenic compound (SM27) that retains the structural and functional properties of the FGF2-binding sequence of TSP-1. Aim: To identify new small molecule inhibitors of FGF2 that recapitulate the structure and functional properties of the FGF-2-binding site of TSP-1, by investigating the chemical space around SM27. Materials and Methods: A similarity-based screening of small molecule libraries has been used to identify candidates, followed by docking calculations, and evaluation of the activity of the resulting compounds in biochemical and biophysical assays, to assess interaction with FGF2, and in experimental models of angiogenesis, to assess biological activity. Results: The used integrated approach allowed selecting 7 bi-naphthalenic compounds that bound FGF2 inhibiting FGF2 binding to both heparan sulfate proteoglycans and FGFR1. The compounds inhibited FGF2-induced endothelial cell proliferation, vessel sprouting from aortic rings and angiogenesis in the chorioallantoic membrane assay, with improved potency over SM27. Conclusions: We have identified new compounds that are valuable as FGF inhibitors for potential therapeutic purposes. Moreover, these compounds are useful chemical tools to identify the minimal stereochemical requirements for FGF2 binding and activity to improve the design of new agents for antineoplastic therapy. Acknowledgement: Supported by AIRC (Associazione Italiana per la Ricerca sul Cancro).